HSV-1 and Alzheimer’s Disease: more than a hypothesis - Roberto ePiacentini; Giovanna eDe Chiara; Domenica Donatella Li Puma; Cristian eRipoli; Maria Elena Marcocci; Enrico eGaraci; Anna Teresa Palamara; Anna Teresa Palamara; Claudio eGrassi (Frontiers in Pharmacology, 2014)
Among the multiple factors concurring to Alzheimer’s Disease (AD) pathogenesis, greater attention should be devoted to the role played by infectious agents. Growing epidemiological and experimental evidence suggests that recurrent herpes simplex virus type-1 (HSV-1) infection is a risk factor for AD although the underlying molecular and functional mechanisms have not been fully elucidated yet. Here, we review literature suggesting the involvement of HSV-1 infection in AD also briefly mentioning possible pharmacological implications of these findings.